Harmonizando interesses : coordenação interna e alinhamento externo dos BRICS - Camila Dafne de Carvalho Ferreira (2024)
The political alignment of the BRICS member countries in the United Nations General Assembly is a crucial aspect for understanding the cohesion and fundaments of the coalition. This study adopts a mixed methods approach, combining the analysis of BRICS summit meeting minutes with voting patterns in the General Assembly, to investigate the internal convergence of the group in this important international forum. The results show that the UNGA is a relevant space for the BRICS, where these countries demonstrate a degree of internal alignment, especially on agendas related to Palestine and economic development. However, this alignment is not uniform, suggesting that the internal convergence of the BRICS may be more instrumental than substantive in certain agendas. Future research is essential to deepen the understanding of the mechanisms of internal cooperation among the BRICS in the UNGA, aiming to identify strategies that promote a more effective and unified performance of the coalition. Additionally, the entry of new countries into the BRICS raises questions about the affinity of interests and the existing internal division, highlighting the need for investigations that assess the unity of interests and goals within the group.